PRÁTICAS PEDAGÓGICAS INTEGRADORAS NO ENSINO MÉDIO INTEGRADO - Santos, F A A; Santos, J D; Professor, V P; Silva, A R (Holos (Natal, RN), 2018)
ABSTRACT In this article we aim to make a study about integrative pedagogical practices used by teachers of the Integrated High School (hereinafter EMI). The analyzes of this work start from fourteen texts that present in their theme educational practices that help in the implementation of the integrated curriculum and can contribute to the training of the subjects involved in the teaching-learning process. The study evidences the need for integrative practices in EMI due to the relevance of its approximation between theory and practice in the integration of disciplines and areas of knowledge, as well as its effective contribution in the consolidation of an integrated curriculum. Instituto Federal de Educaçao, Ciéncia e Tecnologia do Rio Grande do Norte - IFRN; Instituto Federal de Educaçao, Ciéncia e Tecnologia do Maranhao - IFMA; Instituto Federal de Educaçao, Ciéncia e Tecnologia do Mato Grosso - IFMT, Instituto Federal de Educaçao, Ciéncia e Tecnologia Fluminense - IFF; Instituto Federal de Educaçao, Ciéncia e Tecnologia da Bahia - IFBA, Instituto Federal de Educaçao, Ciéncia e Tecnologia Catarinense - IFC e Universidade Regional do Noroeste do Estado do Rio Grande do Sul - UNIJUI.